UPAYA MEMAKNAI KEMBALI CITRA EKS BANDARA KEMAYORAN MELALUI GALERI EDUKASI AVIASI - Santosa, Aaron Pratama; Carina, Nina (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2025)
Kemayoran Airport, built in the 1930s and officially operational on July 8, 1940, is a historic airport that played a significant role in the development of aviation in Indonesia. Constructed by the Dutch East Indies government, it featured modern facilities comparable to European airports of its time. After undergoing various significant historical phases, including the Japanese occupation during the Asia-Pacific War and Indonesia's independence revolution, the airport continued to operate and evolve until its closure on March 31, 1985, due to limitations in accommodating rapid advancements in aviation technology, with the rise of wide-body aircraft and rapid population growth near Kemayoran airfield. Kemayoran Airport subsequently fell into neglect and was replaced by new infrastructure. The traces of Kemayoran Airport’s former glory have almost completely disappeared, rendering it a "placeless" area, with the remaining airport relics in a deteriorated condition. This project seeks to revive the image of aviation through placemaking, envisioning creative aviation-themed spaces for both the public and aviation community. Centered on an educational gallery, it offers diverse aviation-related programs accessible to all age groups and skill levels. The initiative aims to restore the identity of the former Kemayoran Airport with a meaningful function, while fostering awareness, appreciation, and public interest in the importance of aviation. Keywords: aviation; educational gallery; former kemayoran airport; history; placemaking Abstrak Bandara Kemayoran, dibangun sejak 1930-an dan resmi beroperasi 8 Juli 1940, merupakan bandara bersejarah dengan peran penting dalam perkembangan penerbangan di Indonesia. Bandara ini dibangun pemerintah Hindia Belanda dengan fasilitas modern setara bandara di Eropa pada masanya. Setelah melewati berbagai fase sejarah penting, termasuk pendudukan Jepang selama Perang Asia Pasifik dan masa revolusi kemerdekaan Indonesia, bandara ini terus beroperasi dan berkembang hingga akhirnya ditutup pada 31 Maret 1985 karena keterbatasan dalam menampung kemajuan pesat teknologi penerbangan, terutama dengan hadirnya model pesawat berbadan besar yang baru serta meledaknya jumlah populasi penduduk di wilayah sekitar lapangan udara Kemayoran. Bandara Kemayoran kemudian mulai terabaikan dan digantikan oleh infrastruktur baru. Jejak kejayaan Bandara Kemayoran hampir sepenuhnya hilang, menjadikannya sebagai kawasan yang dianggap "placeless", dengan peninggalan bandara yang tersisa dalam kondisi memprihatinkan. Proyek ini bertujuan untuk mengangkat kembali citra aviasi. Melalui metode placemaking akan lahir usulan ruang kreatif berbasis aviasi yang dapat diakses oleh masyarakat umum maupun masyarakat aviasi. Program utama berupa galeri edukasi akan menyediakan berbagai program terkait aviasi, yang dapat diakses oleh masyarakat umum maupun profesional. Melalui upaya ini, diharapkan citra eks Bandara Kemayoran dapat diangkat kembali dengan fungsi baru yang lebih bermakna, sekaligus meningkatkan kesadaran dan minat masyarakat terhadap pentingnya dunia aviasi.